High Performance 3D Si/Ge Nanorods Array Anode Buffered by TiN/Ti Interlayer for Sodium‐Ion Batteries. (14th January 2015) - Yue, Chuang; Yu, Yingjian; Sun, Shibo; He, Xu; Chen, Binbin; Lin, Wei; Xu, Binbin; Zheng, Mingsen; Wu, Suntao; Li, Jing; Kang, Junyong; Lin, Liwei
Abstract : 3D micro/nanobatteries in high energy and power densities are drawing more and more interest due to the urgent demand of them in integrating with numerous micro/nanoscale electronic devices, such as smart dust, miniaturized sensors, actuators, BioMEMS chips, and so on. In this study, the electrochemical performances of 3D hexagonal match‐like Si/Ge nanorod (NR) arrays buffered by TiN/Ti interlayer, which are fabricated on Si substrates by a cost‐effective, wafer scale, and Si‐compatible process are demonstrated and systematically investigated as the anode in sodium‐ion batteries. The optimized Si/TiN/Ti/Ge composite NR array anode displays superior areal/specific capacities and cycling stability by reason of their favorable 3D nanostructures and the effective conductive layers of TiN/Ti thin films. Sodium‐ion insertion behaviors are experimentally investigated in postmorphologies and elemental information of the cycled composite anode, and theoretically studied by the first principles calculation upon the adsorption and diffusion energies of sodium in Ge unit cell. The preferential diffusion of sodium in Ge structure over in Si lattice is evidently proved. The successful configuration of these distinctive wafer‐scale Si‐based Na‐ion micro/nanobattery anodes can provide insight into exploring and designing new Si/Ge‐based electrode materials, which can be integrated into micro‐electronic devices as on chip power systems in the future. Abstract : 3D hexagonal Si/TiN/Ti/Ge NR arrays as anodes in sodium‐ion batteries (SIBs) present high reversible areal/specific capacity and superior cycling stability imposed by high current densities. This kind of unique wafer‐scale 3D Si‐based composite electrode portends a promising future for lab‐on‐chip micro/nanoSIBs with practical applications in integrated circuit systems, micro/nanoelectro mechanical systems, or other smart electronic devices.